2023
DOI: 10.1039/d2nj06318b
|View full text |Cite
|
Sign up to set email alerts
|

Green approach for the synthesis of monolayer reduced graphene oxide: one-step protocol with simultaneous iodination and reduction

Abstract: A schematic representation of iodinated GO and RGO formation in a single step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Zn@ZrO 2 /NG nanocomposites were synthesized based on our previously reported procedure, 20 with novelty in the modification part which was done in a single step. Three different concentrated Zn@ZrO 2 /NG nanocomposites, Zn@ZrO 2 /NG(1 : 5), Zn@ZrO 2 /NG(2 : 5), and Zn@ZrO 2 /NG(3 : 5), were synthesized.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zn@ZrO 2 /NG nanocomposites were synthesized based on our previously reported procedure, 20 with novelty in the modification part which was done in a single step. Three different concentrated Zn@ZrO 2 /NG nanocomposites, Zn@ZrO 2 /NG(1 : 5), Zn@ZrO 2 /NG(2 : 5), and Zn@ZrO 2 /NG(3 : 5), were synthesized.…”
Section: Methodsmentioning
confidence: 99%
“…17 The electrochemical response can be enhanced by modifying the surface of the electrode with an active substance, such as simple metal and metal oxide nanomaterials or nanocomposites. For example, Ag, 18 Au, 19 ZrO 2 , 20 ZnO, AgO 2 , 21 and Fe 2 O 4 22 nanomaterials have great electrochemical detection capability for nitrobenzene because they are excellent catalysts. ZrO 2 nanoparticles are the most suitable materials for immobilizing molecules with oxygen-containing compounds because of their stability at high temperature, inability to react with chemicals, nontoxicity, and strong attraction to oxygen-containing compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we report an iodine‐incorporated graphene material in a one‐pot synthetic methodology by using NaIO 4 and m‐CPBA as oxidizing and iodinating agents at room temperature for supercapacitor application (Figure 1). NaIO 4 is effectively supported in the iodination and oxidation processes, and the effective deoxygenation of i‐GO takes place to produce i‐graphene when m‐CPBA is added to the mixture with H 2 SO 4 via an exothermic process [29] . The iodine functionality on the graphene surface increases the sheet d‐spacing, thereby enhancing the ion mobility and bolstering the cyclic stability of the graphene surface.…”
Section: Introductionmentioning
confidence: 99%
“…NaIO 4 is effectively supported in the iodination and oxidation processes, and the effective deoxygenation of i-GO takes place to produce igraphene when m-CPBA is added to the mixture with H 2 SO 4 via an exothermic process. [29] The iodine functionality on the graphene surface increases the sheet d-spacing, thereby enhancing the ion mobility and bolstering the cyclic stability of the graphene surface. GCD, EIS, and CV studies showed that the i-graphene electrode material displayed a favorable capacitance.…”
Section: Introductionmentioning
confidence: 99%